1981
DOI: 10.1159/000237985
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Metronidazole in Patients with Enteric Disease Compared to Normal Volunteers

Abstract: Tablets of 500 mg metronidazole were given to 24 patients with intestinal diseases and to 10 healthy volunteers. The diagnoses included coeliac disease, ulcerative colitis, jejunoileal shunt, ileostomy, and Crohn’s disease. Both normal subjects and patients exhibited considerable variation in serum metronidazole concentrations. This applied particularly to the patients who had somewhat slower absorption and later occurrence of serum peaks than did the normal subjects. No major deviation occurred within any of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…While serum concentrations of metronidazole in normal individuals were in the same range in all studies [10][11][12][13], differing results were reported for Crohn's disease: Bergan et al [13] found markedly higher metronidazole serum concentra tions in patients with inactive Crohn's dis ease than reported by Melanderet al [14] and higher concentrations than in normal individuals, which has been related to in creased permeability of the diseased intes tinal mucosa for metronidazole. It was therefore of interest to determine serum concentrations of metronidazole and its main metabolite in patients with active Crohn's disease during oral therapy with metronidazole in different dosages and to look for a correlation between individual serum concentrations and disease activity and therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…While serum concentrations of metronidazole in normal individuals were in the same range in all studies [10][11][12][13], differing results were reported for Crohn's disease: Bergan et al [13] found markedly higher metronidazole serum concentra tions in patients with inactive Crohn's dis ease than reported by Melanderet al [14] and higher concentrations than in normal individuals, which has been related to in creased permeability of the diseased intes tinal mucosa for metronidazole. It was therefore of interest to determine serum concentrations of metronidazole and its main metabolite in patients with active Crohn's disease during oral therapy with metronidazole in different dosages and to look for a correlation between individual serum concentrations and disease activity and therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 67%
“…In patients with inactive Crohn's dis ease, Bergan et al [13] found a mean me tronidazole serum concentration of about 13 /rg/ml 2 h after a single oral dose of 500 mg metronidazole, which is distinctly higher than the approximately 7.5 ¿ig/ml found in normal controls receiving the same dosage. This finding has been related to increased permeability of the diseased mucosa for metronidazole in Crohn's dis ease.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This unexpected observation compared to what has been published in literature (Bergan et al, 1981;Houghton et al, 1979) prompted us to perform a complementary study in seven patients, in which the oral administration was replaced by an intravenous infusion (for 3 days). In this situation there were no significant differences between AUCs which therefore ruled out an explanation based on the recovery from surgery of the patients.…”
mentioning
confidence: 71%
“…Confficting data on its absorption are available. Bioavailability studies have suggested either normal (Bergan et al, 1981) or reduced absorption (Melander et al, 1977) but are unreliable due to the lack of study of an intravenous formulation.…”
Section: Introductionmentioning
confidence: 99%